Innovation efficiency, global diversification, and firm value - Gao, Wenlian; Chou, Julia (Journal of Corporate Finance, 2015)
This paper investigates whether multinational firms are less or more efficient in innovation activities than domestic firms. Using patents and citations scaled by R&D expenses and R&D capital as measures of innovation efficiency, we find that multinational firms have lower levels of innovation efficiency than purely domestic firms. This finding has been supported by additional evidence using peer pressure as an exogenous shock to firms' strategy of going international. We also find that information asymmetry and the low cost of capital could be the major channels through which global diversification impacts innovation efficiency adversely. Our results further suggest that innovation efficiency is more valuable to multinational firms that mainly diversify into developed markets or markets with better patent protection.